2022
DOI: 10.3389/fphar.2022.1053210
|View full text |Cite
|
Sign up to set email alerts
|

Precision caffeine therapy for apnea of prematurity and circadian rhythms: New possibilities open up

Abstract: Caffeine is the globally consumed psychoactive substance and the drug of choice for the treatment of apnea of prematurity (AOP), but its therapeutic effects are highly variable among preterm infants. Many of the molecular underpinnings of the marked individual response have remained elusive yet. Interestingly, the significant association between Clock gene polymorphisms and the response to caffeine therapy offers an opportunity to advance our understanding of potential mechanistic pathways. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 379 publications
0
8
0
2
Order By: Relevance
“…From 104 individuals, the results showed that AHR genetic variations (rs1476080 and rs2066853), but not AHRR or ARNT genes, influence caffeine therapy's efficacy. Regarding circadian rhythms in premature infants and AOP management, preterm infants experience ultradian or irregular rhythms during early postnatal life [99]. In kid goats, Piccione et al [100] has reported that the maturity of the circadian rhythm does not mature until the end of the second year of life of the animals.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 104 individuals, the results showed that AHR genetic variations (rs1476080 and rs2066853), but not AHRR or ARNT genes, influence caffeine therapy's efficacy. Regarding circadian rhythms in premature infants and AOP management, preterm infants experience ultradian or irregular rhythms during early postnatal life [99]. In kid goats, Piccione et al [100] has reported that the maturity of the circadian rhythm does not mature until the end of the second year of life of the animals.…”
Section: Future Directionsmentioning
confidence: 99%
“…Moreover, 40-day-old foals have blood pressure immaturity [101], a factor that need to be considered when trying to administer caffeine to neonates. Also, caffeine has been shown to alter circadian rhythms in humans and animals [99]. Novel treatment using caffeine could open a field where caffeine treatment could be coordinated with circadian rhythms to improve disease management and care for premature infants.…”
Section: Future Directionsmentioning
confidence: 99%
“…Caffeine citrate is generally used at a loading dose of 20 mg/kg followed by a maintenance dose of 5-10 mg/kg per day, which may be associated with a reduction in superior mesenteric artery flow for at least 2 hours. However, there is much debate about the optimized dose of this drug, as there is still no consensus defined on this aspect (Dai, et al, 2022;Rebentisch, Kovey, & Denslow, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Следует отметить, что адаптационная инсомния при длительном игнорировании перерастает в психофизиологическую инсомнию и вытекает в нарушение биологических часов организма [2]. Механизмы сна, циркадных ритмов и недугов, связанных с ними, основаны на работе огромного количества внутренних факторов, но основное внимание следует уделить динамике двух гормонов и одного нейромедиатора -кортизола, мелатонина и аденозина [1,3,5].…”
Section: Introductionunclassified
“…Это позволяет организовать биологические функции организма через циркадные ритмы в отношении к изменениям окружения и адаптируя внутреннюю и внешнюю среды. Замеры мелатонина считаются наилучшими индикаторами качества внутренних биологических часов [5].…”
Section: Introductionunclassified